Health systems challenges in cervical cancer prevention program in Malawi - Fresier C. Maseko; Maureen L. Chirwa; Adamson S. Muula (Taylor & Francis Group, 2015)
Background: Cervical cancer remains the leading cause of cancer death among women in sub-Saharan Africa. In Malawi, very few women have undergone screening and the incidence of cervical cancer is on the increase as is the case in most developing countries. We aimed at exploring and documenting health system gaps responsible for the poor performance of the cervical cancer prevention program in Malawi. Design: The study was carried out in 14 randomly selected districts of the 29 districts of Malawi. All cervical cancer service providers in these districts were invited to participate. Two semi-structured questionnaires were used, one for the district cervical cancer coordinators and the other for the service providers. The themes of both questionnaires were based on World Health Organization (WHO) health system frameworks. A checklist was also developed to audit medical supplies and equipment in the cervical cancer screening facilities. The two questionnaires together with the medical supplies and equipment checklist were piloted in Chikwawa district before being used as data collection tools in the study. Quantitative data were analyzed using STATA and qualitative in NVIVO. Results: Forty-one service providers from 21 health facilities and 9 district coordinators participated in the study. Our findings show numerous health system challenges mainly in areas of health workforce and essential medical products and technologies. Seven out of the 21 health facilities provided both screening and treatment. Results showed challenges in the management of the cervical cancer program at district level; inadequate service providers who are poorly supervised; lack of basic equipment and stock-outs of basic medical supplies in some health facilities; and inadequate funding of the program. In most of the health facilities, services providers were not aware of the policy which govern their work and that they did not have standards and guidelines for cervical cancer screening and treatment. Conclusion: Numerous health system challenges are prevailing in the cervical cancer prevention program in Malawi. These challenges need to be addressed if the health system is to improve on the coverage of cervical cancer screening and treatment.